STUDI PENGARUH PERLAKUAN ALKALI DAN PANAS TERHADAP SIFAT MEKANIK SERAT KENAF UNTUK BAHAN KOMPOSIT - Racmat Racmat; Salim Salim (Sekolah Tinggi Maritim Yogyakarta, 2016)
This purpose of the research is to find out the influence of the alkali treatment, the heating and the combinations toward the tensile strength on the kenaf single fiber. The alkali treatment was done by soaking the fibers in the mixture of 99% content of alkali (NaOH) by weight of 60 g and aqua in every litre measured for 3 hours. The heating in this research used temperature of 140 oC for 10 hours while the combination of the two was conducted by soaking the fibers in the mixture of 99% content of alkali (NaOH) by weight of 60 g and aqua in every litre measured for 3 hours, then after the firbers were dry, they were heated at the temperature of 140 oC for 10 hours. The tensile test for single fibre in this research was done by using the standard of ASTM C 1557. The finding of the research showed that the highest tensile strength , was on the combination treatment of 60 g alkali for 3 hours and heat treatment at the temperature of 140 o C for 10 hours in the amount of 23.49 MPa, for alkali treated in the amount 22,35 MPa, and heat treatment in the amount 21,25 MPa. The lowest one was obtained when there was no treatment in the amount of 19.49 MPa